2021
DOI: 10.14710/jitaa.46.3.219-226
|View full text |Cite
|
Sign up to set email alerts
|

Tropical seasonal changes impact on hematological parameters of goats

Abstract: The study was carried out to evaluate the impact of seasonal variations on the hematological responses of goats in Malaysia. Fifty-two goats (24 bucks and 28 does), aged between 1 to 2 years old were used in the study. The goats were fed on commercial concentrate and forage, access to mineral salt and water was ad libitum. Blood samples were obtained from each goat in January, May and September to analyze hematology blood constitute during the study. The results showed that red blood cell (RBC) levels in Anglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
3
3
0
Order By: Relevance
“…Table (5) shows that there were no significant differences for each of (the percentage of hatching from fertilized eggs, the percentage of hatching from total eggs, the percentage of fertilization, the percentage of deaths) compared with the control group for all experimental treatments in the first and second hatching and the rate of the two hatchings, and this is consistent with the results precedent [36].…”
Section: Fertility and Hatching Traitssupporting
confidence: 84%
“…Table (5) shows that there were no significant differences for each of (the percentage of hatching from fertilized eggs, the percentage of hatching from total eggs, the percentage of fertilization, the percentage of deaths) compared with the control group for all experimental treatments in the first and second hatching and the rate of the two hatchings, and this is consistent with the results precedent [36].…”
Section: Fertility and Hatching Traitssupporting
confidence: 84%
“…The findings imply that the addition of folic acid, particularly at high doses, can modify protein structure by partially unfolding it. The literature for bovine serum albumins found similar findings [33]. These findings are agreed with [34].…”
Section: Blood Albuminsupporting
confidence: 83%
“…The increase in LYM concentration in winter as compared to summer in this study is in agreement with Agradi et al (2022) who reported similar results in Verzascese and Camosciata delle Alpi goat breeds in Italy. Dhuha et al (2021) reported an influence of goat breeds (Saanena and Anglo-Nubian) raised in Malaysia on LYM%. MON.…”
Section: Resultsmentioning
confidence: 99%